The role of photosynthesis and amino acid metabolism in the energy status during seed development - Galili, Gad; Avin-Wittenberg, Tamar; Angelovici, Ruthie; Fernie, Alisdair R. (Frontiers in Plant Science, 2014)
Seeds are the major organs responsible for the evolutionary upkeep of Angiosperm plants. Seeds accumulate significant amounts of storage compounds used as nutrients and energy reserves during the initial stages of seed germination. The accumulation of storage compounds requires significant amounts of energy, the generation of which can be limited due to reduced penetration of oxygen and light particularly into the inner parts of seeds. In this review, we discuss the adjustment of seed metabolism to limited energy production resulting from the suboptimal penetration of oxygen into the seed tissues. We also discuss the role of photosynthesis during seed development and its contribution to the energy status of developing seeds. Finally, we describe the contribution of amino acid metabolism to the seed energy status, focusing on the Asp-family pathway that leads to the synthesis and catabolism of Lys, Thr, Met and Ile.